Green procurement implications on the labor market in the context of the transition to the green economy - Daniela Pasnicu; Vasilica Ciuca (Amfiteatru Economic Journal, 2020)
The adoption of green procurement has implications on the labor market because of the changes that occur in the economic structure. The purpose of the article is to contribute to a better understanding of the concept and policies regarding green procurement as well as the implications on the Romanian labor market of the transition to the green economy through green procurement. In this regard, several analyses have been made; an analysis of the current situation, a forecast, on secondary data, of the main trends of the Romanian labor market, compared with those of the EU28, a regression between the number of green jobs and the environmental protection expenditure as well as a cluster analysis in EU 28 countries to capture SMEs' perceptions of resource efficiency and green markets. The analysed data comes from official statistics of EUROSTAT, to which we have added the data from CEDEFOP and those collected within Eurobarometer 381. From the analysis of the data it turned out that there are certain structural imbalances in the labor market in Romania, which could be accentuated by implementing green procurement; a positive relationship at EU level between environmental protection expenditure and green jobs and insignificant differences between countries on green markets and resource efficiency.
Keywords: J; J21; Q; Q57; 330; labor market; green procurement; over-qualification; employment; need for work; green jobs